Modified betel nut residue biochar / chitosan composite adsorbent as well as preparation method and application thereof
By preparing the modified betel nut residue biochar and chitosan composite adsorbent, the problem of unsatisfactory adsorption efficiency of various heavy metal ions in the prior art is solved, and efficient and stable heavy metal ions removal is achieved, with simple operation and cost. Low and environmentally friendly characteristics.
Patent Information
- Application Number
- CN202411547483.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-03
AI Technical Summary
The adsorption efficiency of existing modified biochar adsorbents to a variety of heavy metal ions is not ideal, and the modification method is single, which limits the use of adsorbents.
The betel nut residue powder was modified by CaCl2 and H2O2 to prepare modified betel nut residue biochar, and the modified betel nut residue biochar/chitosan was reacted with chitosan in glacial acetic acid solution and glutaraldehyde was added to form the modified betel nut residue biochar/chitosan composite. Adsorbent, increasing the adsorption active site and mechanical strength.
It improves the adsorption rate of a variety of heavy metal ions, improves the stability and mechanical strength of the adsorbent, and realizes efficient removal of Cd2+, Cu2+, and Pb2+ in wastewater. It is simple to operate, low cost, easy to obtain materials, and low energy consumption. No secondary pollution occurs.
Smart Images

Figure CN119236887A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorbent material preparation, and in particular to a modified betel nut residue biochar / chitosan composite adsorbent and a preparation method and application thereof. Background Art
[0002] With the rapid advancement of industrialization and urbanization in my country, water pollution has become a serious problem, especially heavy metal pollution. The treatment methods for heavy metal wastewater include chemical precipitation, ion exchange, membrane separation, solvent extraction, electrolysis, adsorption, etc. Among them, the chemical precipitation method will produce a large amount of sludge, the ion exchange method has a high cost and poor resin regeneration, the membrane separation method has high efficiency and good stability, but the membrane has a short life and high investment cost, the solvent extraction method has good separation effect and strong selectivity, but its extractant is expensive and the energy loss in the extraction process is large, the electrolysis method is efficient and environmentally friendly, but there are problems such as high electrolysis energy consumption and equipment corrosion. In contrast, the adsorption method has the characteristics of simple operation, low cost and easy availability of materials during the treatment process.
[0003] Biochar contains two components: organic matter and inorganic minerals. The organic components are mainly alkyl and aromatic structures composed of elements such as C, H, O, and N, including groups such as carboxyl, phenolic hydroxyl, and carbonyl anhydride; the inorganic components include amorphous and crystalline minerals composed of elements such as Na, K, Ca, P, and Mg. Due to these special structures of biochar-based materials, it has become a new type of wastewater treatment material with excellent performance and broad development and application prospects. Some researchers have conducted modification research on biochar adsorbents to improve their adsorption performance. However, most of the modified biochar adsorbents currently target the adsorption of one heavy metal ion, and the adsorption of multiple heavy metal ions is relatively rare, and the adsorption efficiency is not ideal; in addition, the modification method is single, usually using one method for modification, with fewer adsorption active sites, which limits the use of the adsorbent. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a modified betel nut residue biochar / chitosan composite adsorbent, and the prepared adsorbent has a good adsorption effect on various heavy metal ions.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing a modified betel nut residue biochar / chitosan composite adsorbent, comprising the following steps: S1. Use CaCl 2 The betel nut residue powder is modified by using a solution to obtain a modified powder, and the modified powder is carbonized to obtain a carbonized product, and then H 2 O 2 The solution is used to modify the carbonized product to obtain modified betel nut residue biochar; S2. Mix chitosan and modified betel nut residue biochar in a glacial acetic acid solution to obtain a mixed solution, add glutaraldehyde to the mixed solution, and obtain a modified betel nut residue biochar / chitosan composite adsorbent after reaction.
[0006] The betel nut bagasse powder can be obtained by the following method: grinding green betel nut fruit into powder to obtain betel nut bagasse powder. Specifically, the green betel nut fruit is washed, dried and dried, and then broken, ground, and sieved (for example, through a 100-mesh sieve) to obtain the betel nut bagasse powder.
[0007] Furthermore, in step S1, every 20-40 g of betel nut residue powder corresponds to 1 L of CaCl 2 For example, the dosage of the betel nut residue powder is 20-40 g, and the CaCl 2 The amount of solution used is 1 L. Among them, 20-40 g includes but is not limited to 20 g, 30 g, and 40 g.
[0008] Furthermore, in step S1, the temperature for carbonizing the modified powder is 500-700°C, wherein 500-700°C includes but is not limited to 500°C, 600°C, and 700°C.
[0009] Furthermore, in step S1, 30 to 70 mL H 2 O 2 For example, the amount of the carbonized product is 5 g, and the H 2 O 2 The dosage of the solution is 30 to 70 mL, wherein 30 to 70 mL includes but is not limited to 30 mL, 40 mL, 50 mL, 60 mL, and 70 mL.
[0010] Furthermore, in step S2, every 0.3-1.5g of modified betel nut residue biochar corresponds to 2g of chitosan, 100mL of glacial acetic acid solution and 2-7mL of glutaraldehyde. For example, the amount of the modified betel nut residue biochar is 0.3-1.5g, the amount of the chitosan is 2g, the amount of the glacial acetic acid solution is 100mL, and the amount of the glutaraldehyde is 2-7mL. Among them, 0.3-1.5g includes but is not limited to 0.3g, 0.6g, 1g, 1.2g, 1.5g; 2-7mL includes but is not limited to 2mL, 3mL, 4mL, 5mL, 6mL, 7mL.
[0011] Furthermore, in step S2, the temperature of the mixed solution is 40-80°C, wherein 40-80°C includes but is not limited to 40°C, 50°C, 60°C, 70°C, and 80°C.
[0012] The pH value can be adjusted to be neutral after the mixed solution and glutaraldehyde react for 60 minutes, for example, by using a sodium hydroxide solution to adjust the pH value to be neutral.
[0013] Another object of the present invention is to provide a modified betel nut residue biochar / chitosan composite adsorbent, which is prepared by the above-mentioned preparation method.
[0014] In addition, the modified betel nut residue biochar / chitosan composite adsorbent can be used in the adsorption of heavy metal ions in water. Specifically, it can be used to adsorb heavy metal ions in water containing Cd 2+ , Cu 2+ , Pb 2+ The modified betel nut residue biochar / chitosan composite adsorbent is added to the solution to adsorb heavy metal ions in the solution.
[0015] Furthermore, each 150 mL contains 10 to 50 mg / L of heavy metal ions Cd 2+ , Cu 2+ , Pb 2+ The solution corresponds to 0.5-2.5 g of modified betel nut residue biochar / chitosan composite adsorbent. For example, the amount of the solution is 150 mL and contains 10-50 mg / L of heavy metal ions Cd 2+ , Cu 2+ , Pb 2+ The dosage of the modified betel nut residue biochar / chitosan composite adsorbent is 0.5-2.5g. Among them, 10-50mg / L includes but is not limited to 10mg / L, 20mg / L, 30mg / L, 40mg / L, 50mg / L; 0.5-2.5g includes but is not limited to 0.5g, 1g, 1.5g, 2.0g, 2.5g.
[0016] Furthermore, the heavy metal ion Cd 2+ , Cu 2+ , Pb 2+ The temperature of the solution is 30-70°C, and the modified betel nut residue biochar / chitosan composite adsorbent adsorbs heavy metal ions in the solution for 4-8 hours. 30-70°C includes but is not limited to 30°C, 40°C, 50°C, 60°C, and 70°C; 4-8 hours includes but is not limited to 4 hours, 5 hours, 6 hours, 7 hours, and 8 hours.
[0017] Compared with the existing biochar adsorbent, the present invention has the following advantages: 1. The present invention uses calcium chloride (CaCl 2 ), hydrogen peroxide (H 2 O 2 ) The betel nut residue is modified to prepare modified betel nut residue biochar, so that the porosity of the betel nut residue biochar is improved and the effective oxygen-containing functional groups are increased.
[0018] 2. The present invention introduces chitosan with rich functional groups into the modified betel nut residue biochar through glutaraldehyde cross-linking, providing a large number of active adsorption points for the adsorbent, such as carboxyl, hydroxyl, amine, carbonyl, etc., which can solve the problem of simultaneous adsorption of multiple heavy metal ions in wastewater and low adsorption rate, and also improves the mechanical strength and stability of the adsorbent.
[0019] 3. The modified composite adsorbent prepared by the present invention has the characteristics of simple operation, low cost, easy availability of materials, stable operation effect, low energy consumption, no secondary pollution, and the adsorbent can be recycled through a suitable desorption process, thereby achieving the purpose of treating waste with waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM image of the modified betel nut residue biochar / chitosan composite adsorbent prepared in Example 1; Figure 2 The infrared spectra of the betel nut residue powder and the modified betel nut residue biochar / chitosan composite adsorbent (i.e., before and after the adsorbent is modified) prepared in Example 1; Figure 3 This is a SEM image of the modified betel nut residue biochar / chitosan composite adsorbent prepared in Example 1 after adsorption of heavy metal ions; Figure 4 The adsorbent prepared in Example 1 is 2+ , Cu 2+ , Pb 2+ Concentration removal effect diagram. DETAILED DESCRIPTION
[0021] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with the examples, and the contents mentioned in the examples are not limitations of the present invention. It should be noted in advance that the following examples were completed in the laboratory, and those skilled in the art should understand that the amounts of the components given in the examples only represent the ratio relationship between the components, rather than specific limitations.
[0022] Areca nut residue contains many crude fiber tissues and minerals, including about 53.20% of α-cellulose, 30%-64.8% of hemicellulose, 7%-24.8% of lignin, etc. The hard shell (epidermis) of betel nut accounts for 60%-80% of the weight and volume of the whole fruit, while hemicellulose and lignin in the shell fiber account for 35%-64.8% and 13.0%-26.0% respectively. These organic active substances contain functional groups such as carboxyl and hydroxyl groups, which have a certain adsorption effect on heavy metal ions, but the adsorption capacity is low.
[0023] To this end, the present invention proposes a method for preparing a modified betel nut residue biochar / chitosan composite adsorbent. The prepared adsorbent has a good adsorption effect on various heavy metal ions. Example 1
[0024] 1. Preparation of modified betel nut residue biochar Raw materials: betel nut, chitosan, calcium chloride (CaCl 2 ), hydrogen peroxide (H 2 O 2 ), glacial acetic acid, glutaraldehyde, water.
[0025] 1. Pretreatment of Areca Nut Select fresh green betel nut fruits, wash them, wipe off the moisture, dehydrate and dry them in a blast drying oven, and then break them with a wall breaking machine, grind them, and pass them through a 100-mesh sieve to obtain betel nut residue powder.
[0026] 2. Preparation of modified betel nut residue biochar Weigh 30 g of betel nut residue powder and place it in 1L CaCl 2 The solution was immersed for 24 h, filtered, dried, and ground through a 100-mesh sieve to obtain powder A (i.e., modified powder). Powder A was placed in a tube furnace in an oxygen-deficient or oxygen-free environment (N 2 The heating rate was set to 10 °C / min, the temperature was set to 600 °C, the holding time was set to 120 min, and the biochar was cooled. The biochar was washed, dried, ground, and passed through a 100-mesh sieve to obtain a carbonized product, which was recorded as B. Weigh 5 g of the carbonized product B and place it in 50 mL of H 2 O 2 The solution was reacted at room temperature for 12 h, filtered, washed, dried, ground, and passed through a 100-mesh sieve to obtain modified betel nut residue biochar, which was recorded as C.
[0027] 2. Preparation of modified betel nut residue biochar / chitosan composite adsorbent material Weigh 2 g of chitosan and 1 g of modified betel nut residue biochar C, mix and stir in 100 mL of glacial acetic acid solution, pour the mixture into a three-necked flask, heat in a constant temperature water bath at 60 °C, stir, add 5 mL of glutaraldehyde dropwise, react for 60 min, adjust the pH to neutral with sodium hydroxide solution, keep the temperature constant throughout the reaction process, and after the reaction is completed, filter, dry, grind and sieve to obtain the modified betel nut residue biochar / chitosan composite adsorbent, recorded as D.
[0028] Figure 1 This is the SEM image of adsorbent D. It can be seen from the figure that the prepared adsorbent D has many and evenly distributed voids, and its structure is similar to circular holes.
[0029] Figure 2The infrared spectra of the adsorbent before and after modification are shown. It can be seen from the figure that at 3500 cm -1 The absorption peak near -NH 2 The stretching vibration absorption peak of -OH and -OH is at 3500 cm -1 The vibration near the surface is more obvious, indicating that the modified chitosan effectively adsorbs the functional group -NH 2 and -OH increased significantly. At 1600 cm -1 The absorption peak near -NH 2 The bending vibration of indicates that there are a large number of active amino groups on the modified chitosan functional groups.
[0030] Combination Figure 1 , Figure 2 It can be seen that this embodiment prepared an adsorbent material with stability and high adsorption.
[0031] 3. Adsorption of heavy metal ions by modified betel nut residue biochar / chitosan composite adsorbent 150 mL of heavy metal ion Cd containing 20 mg / L 2+ , Cu 2+ , Pb 2+ The solution was added to a conical flask, 1 g of adsorbent D was added thereto, and the mixture was shaken at 50 °C and 180 r / min for 6 h. After sampling with a syringe, the solution was filtered through a 0.45 μm aqueous phase needle filter, and the Cd content in the solution was determined by inductively coupled plasma optical emission spectrometry (ICP-OES). 2+ , Cu 2+ , Pb 2+ concentration, and the calculated removal rates were 92.1%, 97.0%, and 98.3%, respectively.
[0032] Figure 3 This is the SEM picture of the composite adsorbent D adsorbing heavy metal ions. It can be seen from the figure that a large amount of heavy metal ions are adsorbed in the corresponding pore structure of the composite adsorbent D.
[0033] Figure 4 It shows the adsorption capacity of the adsorbent for heavy metal ions. It can be seen that the modified composite adsorbent D has strong adsorption capacity for heavy metal ions and high adsorption efficiency. Figure 3 be consistent.
[0034] 4. Adsorbent Regeneration Test In order to study the regeneration performance of the adsorbent, 1 mol / L NaCl solution was used to adsorb Cd 2+ , Cu 2+ , Pb 2+The adsorbent was desorbed, washed, dried, and adsorbed for 5 cycles with a desorption time of 120 min. The test found that the adsorbent had no obvious changes and had high stability. Example 2
[0035] The main difference between this embodiment and embodiment 1 is that the betel nut residue powder is 20 g, and the carbonization temperature and other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 73.5%, 76.2% and 80.6%. Example 3
[0036] The main difference between this embodiment and embodiment 1 is that the betel nut residue powder is 40 g, and the carbonization temperature and other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 75.9%, 78.7% and 83.2%. Example 4
[0037] The main difference between this embodiment and embodiment 1 is that the carbonization temperature is 500°C, and the other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 72.8%, 76.3% and 82.5%. Example 5
[0038] The main difference between this embodiment and embodiment 1 is that the carbonization temperature is 700°C, and the other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 75.2%, 79.6% and 85.4%. Example 6
[0039] The main difference between this embodiment and embodiment 1 is that H 2 O 2 The solution volume was 30 mL, and the carbonization temperature and other conditions were the same as those in Example 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 70.0%, 72.3% and 72.9%. Example 7
[0040] The main difference between this embodiment and embodiment 1 is that H 2 O 2The solution volume was 40 mL, and the carbonization temperature and other conditions were the same as those in Example 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 76.3%, 79.6% and 82.3%. Example 8
[0041] The main difference between this embodiment and embodiment 1 is that H 2 O 2 The solution volume was 60 mL, and the carbonization temperature and other conditions were the same as those in Example 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 78.8%, 82.8% and 88.1%. Example 9
[0042] The main difference between this embodiment and embodiment 1 is that H 2 O 2 The solution volume was 70 mL, and the carbonization temperature and other conditions were the same as those in Example 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 77.3%, 81.5% and 86.1%. Example 10
[0043] The main difference between this embodiment and embodiment 1 is that 2 g chitosan and 0.3 g modified betel nut residue biochar C are weighed and mixed in 100 mL glacial acetic acid solution, and the other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 69.1%, 73.6% and 72.5%. Embodiment 11
[0044] The main difference between this embodiment and embodiment 1 is that 2 g chitosan and 0.6 g modified betel nut residue biochar C are weighed and mixed in 100 mL glacial acetic acid solution, and the other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 74.7%, 78.2% and 82.6%. Example 12
[0045] The main difference between this embodiment and embodiment 1 is that 2 g chitosan and 1.2 g modified betel nut residue biochar C are weighed and mixed in 100 mL glacial acetic acid solution, and the other conditions are the same as those in embodiment 1. 2+ , Cu2+ , Pb 2+ The removal rates were 78.6%, 81.9% and 88.1%. Embodiment 13
[0046] The main difference between this embodiment and embodiment 1 is that 2 g chitosan and 1.5 g modified betel nut residue biochar C are weighed and mixed in 100 mL glacial acetic acid solution, and the other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 75.1%, 77.5% and 84.7%. Embodiment 14
[0047] The main difference between this embodiment and embodiment 1 is that the mixture is heated in a 40°C constant temperature water bath, stirred, and 5 mL of glutaraldehyde is added dropwise. The other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 70.0%, 75.3% and 79.5%. Embodiment 15
[0048] The main difference between this embodiment and embodiment 1 is that the mixture is heated in a 50°C constant temperature water bath, stirred, and 5 mL of glutaraldehyde is added dropwise. The other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 73.0%, 79.9% and 82.5%. Example 16
[0049] The main difference between this embodiment and embodiment 1 is that the mixture is heated in a 70°C constant temperature water bath, stirred, and 5 mL of glutaraldehyde is added dropwise. The other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 76.5%, 81.4% and 84.6% respectively. Embodiment 17
[0050] The main difference between this embodiment and embodiment 1 is that the mixture is heated in a constant temperature water bath at 80°C, stirred, and 5 mL of glutaraldehyde is added dropwise. The other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 72.7%, 78.5% and 80.2%. Embodiment 18
[0051] The main difference between this embodiment and embodiment 1 is that the mixture is heated in a 60°C constant temperature water bath, stirred, and 2 mL of glutaraldehyde is added dropwise. The other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 68.5%, 73.1% and 76.7%. Embodiment 19
[0052] The main difference between this embodiment and embodiment 1 is that the mixture is heated in a 60°C constant temperature water bath, stirred, and 3 mL of glutaraldehyde is added dropwise. The other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 72.3%, 75.5% and 79.9%. Embodiment 20
[0053] The main difference between this embodiment and embodiment 1 is that the mixture is heated in a 60°C constant temperature water bath, stirred, and 4 mL of glutaraldehyde is added dropwise. The other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 75.6%, 78.3% and 82.5%. Embodiment 21
[0054] The main difference between this embodiment and embodiment 1 is that the mixture is heated in a 60°C constant temperature water bath, stirred, and 6 mL of glutaraldehyde is added dropwise. The other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 78.4%, 82.9% and 88.2%. Embodiment 22
[0055] The main difference between this embodiment and embodiment 1 is that the mixture is heated in a 60°C constant temperature water bath, stirred, and 7 mL of glutaraldehyde is added dropwise. The other conditions are the same as those in embodiment 1. 2+ , Cu 2+ , Pb 2+ The removal rates were 78.8%, 83.1% and 88.5%. Embodiment 23
[0056] The main difference between this embodiment and embodiment 1 is that the adsorbent for the adsorption of heavy metal ions uses 150 mL of a 10 mg / L heavy metal ion Cd 2+ , Cu 2+ , Pb 2+ The other conditions were the same as those in Example 1. After testing, the final Cd 2+, Cu 2+ , Pb 2+ The removal rates were 80.2%, 84.5% and 88.9%. Embodiment 24
[0057] The main difference between this embodiment and embodiment 1 is that the adsorbent for the adsorption of heavy metal ions uses 150 mL of a 30 mg / L heavy metal ion Cd 2+ , Cu 2+ , Pb 2+ The other conditions were the same as those in Example 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 91.0%, 93.2% and 95.3%. Embodiment 25
[0058] The main difference between this embodiment and embodiment 1 is that the adsorbent for the adsorption of heavy metal ions uses 150 mL of a 40 mg / L heavy metal ion Cd 2+ , Cu 2+ , Pb 2+ The other conditions were the same as those in Example 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 85.9%, 86.4% and 87.3%. Embodiment 26
[0059] The main difference between this embodiment and embodiment 1 is that the adsorbent for the adsorption of heavy metal ions uses 150 mL of a 50 mg / L heavy metal ion Cd 2+ , Cu 2+ , Pb 2+ The other conditions were the same as those in Example 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 80.6%, 83.7% and 82.3%. Embodiment 27
[0060] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 0.5 g of the adsorbent was added to a conical flask and shaken at 50 °C and 180 r / min for 6 h. The other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 76.3%, 79.2% and 81.1%. Embodiment 28
[0061] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 1.5 g of the adsorbent was added to a conical flask and shaken at 50 °C and 180 r / min for 6 h. The other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 92.5%, 97.3% and 98.5%. Embodiment 29
[0062] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 2.0 g of the adsorbent was added to a conical flask and shaken at 50 °C and 180 r / min for 6 h. The other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 93.0%, 97.5% and 98.6%. Embodiment 30
[0063] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 2.5 g of the adsorbent was added to a conical flask and shaken at 50 °C and 180 r / min for 6 h. The other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 93.1%, 97.7% and 98.8%. Embodiment 31
[0064] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 1.0 g of the adsorbent was added to a conical flask and shaken at 30 °C and 180 r / min for 6 h. The other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 81.2%, 84.9% and 88.6%. Embodiment 32
[0065] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 1.0 g of the adsorbent was added to a conical flask and shaken at 40 °C and 180 r / min for 6 h. Other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 84.7%, 89.6% and 91.5%. Embodiment 33
[0066] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 1.0 g of the adsorbent was added to a conical flask and shaken at 60 °C and 180 r / min for 6 h. Other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 91.8%, 96.5% and 97.7%. Embodiment 34
[0067] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 1.0 g of the adsorbent was added to a conical flask and shaken at 70 °C and 180 r / min for 6 h. The other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 86.1%, 89.9% and 91.2%. Embodiment 35
[0068] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 1.0 g of the adsorbent was added to a conical flask and shaken at 50 °C and 180 r / min for 4 h. The other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 78.2%, 83.4% and 88.5%. Embodiment 36
[0069] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 1.0 g of the adsorbent was added to a conical flask and shaken at 50 °C and 180 r / min for 5 h. The other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 85.6%, 90.7% and 92.4%. Embodiment 37
[0070] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 1.0 g of the adsorbent was added to a conical flask and shaken at 50 °C and 180 r / min for 7 h. Other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+The removal rates were 92.2%, 97.3% and 98.6%. Embodiment 38
[0071] The main difference between this embodiment and embodiment 1 is that, for the adsorption of heavy metal ions by the adsorbent, 1.0 g of the adsorbent was added to a conical flask and shaken at 50 °C and 180 r / min for 8 h. Other conditions were the same as those in embodiment 1. After testing, the final Cd 2+ , Cu 2+ , Pb 2+ The removal rates were 92.8%, 97.6% and 98.5%.
[0072] It can be seen from the above examples that the process of preparing the adsorbent of the present invention is simple, the raw materials are cheap and easy to obtain, the reaction process is easy to control, the prepared adsorbent is stable, can be reused, and will not cause secondary pollution. By modifying and cross-linking chitosan with glutaraldehyde as a cross-linking agent, not only the surface area of the composite adsorbent is increased, the aperture ratio is increased, and the effective oxygen-containing functional groups are increased, but also amino groups, acetylamino groups, etc. are introduced, so that it has better adsorption performance and is effective for heavy metal ions Cd 2+ , Cu 2+ , Pb 2+ The adsorption rate is more than 90%. Compared with the existing heavy metal treatment methods, such as chemical method, electrolysis method, flocculation method, etc., secondary pollution and high energy consumption will be caused, while the adsorption method has few adsorption active sites, small specific surface area, and few effective adsorption active functional groups. The present invention has a wide source of raw materials, low cost, and is green and environmentally friendly. It not only increases the physical adsorption capacity of the adsorbent, but also improves the chemical adsorption capacity of the adsorbent. It has good potential and broad application prospects for sewage treatment.
[0073] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.
[0074] Finally, it should be emphasized that in order to allow ordinary technicians in the field to more easily understand the improvements of the present invention over the prior art, some descriptions of the present invention have been simplified, and for the sake of clarity, some other elements are omitted in this application document. Those skilled in the art should realize that these omitted elements may also constitute the content of the present invention.
Claims
1. A method for preparing a modified betel nut residue biochar / chitosan composite adsorbent, characterized in that: The following steps are involved: S1, using a CaCl2 solution to modify betel nut bagasse powder to obtain a modified powder, then carbonizing the modified powder to obtain a carbonized product, and then using a H2O2 solution to modify the carbonized product to obtain modified betel nut bagasse biochar; S2. Mix chitosan and modified betel nut residue biochar in a glacial acetic acid solution to obtain a mixed solution, add glutaraldehyde to the mixed solution, and obtain a modified betel nut residue biochar / chitosan composite adsorbent after reaction.
2. The method for preparing the modified betel nut residue biochar / chitosan composite adsorbent according to claim 1, characterized in that: In step S1, every 20 to 40 g of betel nut residue powder corresponds to 1 L of CaCl2 solution.
3. The method for preparing the modified betel nut residue biochar / chitosan composite adsorbent according to claim 1, characterized in that: In step S1, the temperature for carbonizing the modified powder is 500-700°C.
4. The method for preparing the modified betel nut residue biochar / chitosan composite adsorbent according to claim 1, characterized in that: In step S1, every 5 g of carbonized product corresponds to 30 to 70 mL of H2O2 solution.
5. The method for preparing the modified betel nut residue biochar / chitosan composite adsorbent according to claim 1, characterized in that: In step S2, every 0.3-1.5 g of modified betel nut bagasse biochar corresponds to 2 g of chitosan, 100 mL of glacial acetic acid solution and 2-7 mL of glutaraldehyde.
6. The method for preparing the modified betel nut residue biochar / chitosan composite adsorbent according to claim 1, characterized in that: In step S2, the temperature of the mixed solution is 40-80°C.
7. A modified betel nut residue biochar / chitosan composite adsorbent, characterized in that: The composite adsorbent is prepared by the method for preparing the modified betel nut residue biochar / chitosan composite adsorbent described in any one of claims 1 to 6.
8. The use of the modified betel nut residue biochar / chitosan composite adsorbent according to claim 7 in adsorbing heavy metal ions in water, characterized in that: To heavy metal ions Cd 2+ , Cu 2+ , Pb 2+ The modified betel nut residue biochar / chitosan composite adsorbent is added to the solution to adsorb heavy metal ions in the solution.
9. The use of the modified betel nut residue biochar / chitosan composite adsorbent according to claim 8 in adsorbing heavy metal ions in water, characterized in that: Each 150mL contains 10~50mg / L heavy metal ion Cd 2+ , Cu 2+ , Pb 2+ The solution corresponds to 0.5 to 2.5 g of modified betel nut residue biochar / chitosan composite adsorbent.
10. The use of the modified betel nut residue biochar / chitosan composite adsorbent according to claim 8 in adsorbing heavy metal ions in water, characterized in that: The heavy metal ion Cd 2+ , Cu 2+ , Pb 2+ The temperature of the solution is 30 to 70° C., and the modified betel nut residue biochar / chitosan composite adsorbent adsorbs heavy metal ions in the solution for 4 to 8 hours.
Citation Information
Cited By
Chitosan modified cyanobacteria biochar material as well as preparation method and application thereof
CN119972017A
